(untitled) (Herald of Journalism, 2024)
Modern film production, including documentary filmmaking, is seeking alternative solutions for financial issues. Documentary filmmaking is actively developing, as the young generation watches films on smart devices, leading to an increasing demand for the production of new projects. Crowdfunding is gaining significant traction in financing documentary films. In Western countries, crowdfunding has shown significant success, and Kazakhstani directors are adopting new project realization opportunities based on these examples. Based on the classical understanding of crowdfunding as the financing of projects through the use of Internet, aiming to attract small contributions from a large number of people, the author of this research sets the objective to delineate crowdfunding as an alternative means of financing documentary films and supporting independent film production. By studying successful crowdfunding campaigns, analyzing challenges and opportunities, the article presents the potential of crowdfunding as a means of financing and distributing independent documentary films, using Kazakhstan and Turkey as examples. A study of crowdfunding platforms in several countries is also analyzed. It provides insights into the evolving landscape and the potential of crowdfunding to support independent film production. It is noteworthy that the value of crowdfunding lies in providing women directors in countries where it was previously impossible to receive funding for their projects. Crowdfunding is becoming a popular way for financing documentary films, providing an alternative to traditional sources such as grants, sponsorship and investments. This research in the field of documentary filmmaking and crowdfunding may be useful for journalism faculties, media and film industry practitioners.